The Implementation Of Lesson Study To Improve The Teaching Quality Of Science And Mathematics Teachers at Secondary Schools Dato' Syed Ahmad - Humnah, Almira Nailal; Rohmah, Zakia Nor (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study explores the implementation of Lesson Study as a professional development approach aimed at enhancing the teaching quality of Science and Mathematics teachers at Secondary Schools Dato' Syed Ahmad. The Lesson Study model involves a cyclical process of collaborative planning, classroom observation, and reflective discussion among teachers. Through qualitative and quantitative methods, data were collected via interviews, classroom observations, and teaching performance assessments before and after the implementation. The findings indicate significant improvements in lesson planning, instructional strategies, and student engagement. Teachers reported that collaborative lesson planning allowed them to share diverse pedagogical insights and design more effective learning activities. Classroom observations revealed increased use of inquiry-based and student-centered approaches, particularly in conceptual topics. Furthermore, reflective sessions encouraged teachers to critically analyze their teaching practices and continuously refine their methods. This process cultivated a culture of collegiality and continuous improvement within the teaching staff. The study concludes that Lesson Study has a positive impact on the professional competencies of Science and Mathematics teachers, leading to better student outcomes and a more dynamic classroom environment. As a sustainable model, Lesson Study is recommended for broader implementation across Malaysian secondary schools to foster a culture of pedagogical excellence and reflective teaching practices.